Respostas

2014-03-27T13:47:07-03:00
X + Y= 3/4                                                             X=3/4 -1/2
X  - Y= 1/4                                                             x =3 /4 - 2/4   
                                                                             x= 1/4
X=3/4-Y Coloque em evidência          
                                                                               X + Y=3/4
3/4-Y=1/4                                                                1/4 + 1/2 =3/4                       
-Y=1/4-3/4                                                               1+2 /4    3/4=3/4
-Y=-1/2   (-1)
 Y=1/2